Singing Performance Arts Formation: The Significance of Education and the Creative Development of Youth - Temirbaev, Begis (Indonesian Journal Publisher, 2025)
This article analyzes the main approaches to the art of singing and its formation and development among student youth. The performance of songs serves not only to teach sound techniques, but also to develop the creative potential of young people, express their feelings, and enhance their social skills. The article presents important ideas about the importance of song performance in education, cultural and spiritual development, personal expression, team performance, and the emotional development of young people. Research and the integration of theoretical and practical training demonstrate that the art of singing serves as an important tool for adapting young people to society and understanding their inner world. The article also emphasizes the role of song performance in the spiritual and aesthetic enrichment of youth.